Optimizing Ammonia Removal from Secondary Aluminum Dross as a Potential Raw Material Substitution in the Cement Industry - Prihartanto Prihartanto; Manis Yuliani; Wahyu Purwanta; Wiharja Wiharja; Muhammad Hanif; Naufal Riadhi Yusuf; Nida Sopiah; Priska Alfatri Hendrayanto; Sophia Shanti Meilani (International Journal of Engineering and Technology Innovation, 2025)
Secondary aluminum dross (SAD), produced by small and medium-sized enterprises in Jombang Regency, Indonesia, is a hazardous waste with high ammonia content that threatens the environment and human health. Although SAD has potential as an alumina source for cement production, ammonia emissions restrict its safe use. This study applies a simultaneous heat-stirred alkaline leaching method to optimize ammonia removal for use as raw material in cement manufacturing. It addresses gaps in single-factor studies by optimizing multiple factors (NaOH concentration, temperature, reaction time, and stirring speed) using the Box–Behnken Design within Response Surface Methodology. Temperature and reaction time are the most influential, while interactions between NaOH and temperature, and between temperature and stirring speed, are critical for maximizing removal. The optimized process removed 98.81% ammonia, while an alternative yielded 98.34% with lower chemical and energy inputs. It enables safe SAD reuse and promotes the circular economy through waste valorization.